PENGARUH KERAGAMAN PRODUK, HARGA DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO RANI LOUHAN DI PAYANGAN BALI - Kusnadi, Edy; Tulhusnah, Lusiana; Minullah, Minullah; Pramesthi, Riska Ayu (Relawan Jurnal Indonesia, 2022)
Based on the results of multiple linear regression, it shows that the variables of product diversity (X1), price (X2) and location (X3). Y = -6.236E-16 + 0.248X1 + 0.568X2 + 0, 193X3 + e. The tcount for this product diversity variable is 5.092. While the value in the 5% distribution ttable is 1.986, then tcount 5.092 > t-table 1.986 means Ho is rejected or Ha is accepted. The t-count value for this Price variable is 10.290. While the value in the 5% distribution ttable is 1.986, then t-count 10.290 > 1.986 t table means Ho is rejected or Ha is accepted. Meanwhile, the t-count value for this location variable is 3.553. While the value in the 5% distribution t-table is 1.986, then t-count 3,553 > t-table 1,986 means Ho is rejected or Ha is accepted. Comparing the F-count (858.931) > Ftable (2.70) based on statistical testing using the f test method, where the significant level obtained is 0.000 < 0.05. Showing the value of the coefficient of determination R square shows a value of 0.966, from these results it means that all independent variables (Diversity of products, prices, and locations) have a contribution of 96.6% to the dependent variable (purchase decisions) with a sufficient level of determination, and the remaining 3,4% influenced by other factors not included in the study